Education Financing Management at Modern Islamic Boarding School in Medan - Candra Wijaya; Muhammad Iqbal; Ahmad Mukhlasin; Muhammad Rizki Syahputra; Sudirman Sudirman (STAI Hubbulwathan Duri, 2022)
This study aims to provide an overview of education financing management at Ta'dib Al-Syakirin Modern Islamic Boarding School, Medan. The method used in this study is a qualitative policy analysis method. Data was gathered through observation, in-depth interviews, and documentation. The findings revealed that Ta'dib Al-Syakirin Modern Islamic Boarding School Medan's education financing was managed in three stages. The three stages are as follows: (1). Planning entails creating work schedules and budgets for Ta'dib Al-Syakirin Modern Islamic Boarding School Medan. (2). Implementation entails: a) Education Financing Sources at Ta'dib Al-Syakirin Modern Islamic Boarding School, Medan: Education funding is derived from students' monthly and annual educational development contributions, as well as unrestricted non-donors. b). Implementation of Education Financing at Ta'dib Al-Syakirin Modern Islamic Boarding School, Medan; Fixed costs in education include the salaries of all educators and education personnel; electrical power services; water; Wi-Fi (internet network) providing equipment for stationery shopping; and non-routine cost requirements such as the cost of repairing facilities and infrastructure due to disaster damage or the period of resilience of goods; and maintenance of Islamic boarding school goods. (3) The evaluation includes the agency's accountability audit report; the repair is carried out in two stages over the course of a year.